(untitled) (Iter, 2022)
In Píndaro’s First Pythian ode, the presence of becomes relevant on the first two triads. The ode begins with the description of the queen of birds, who remains under the spell of the lyre and the dance, as in a reverie. From above, the bird remains lethargic on the scepter of Zeus, as a symbol of the sublime and contemplates, at a certain distance, the world of human beings. As a metaphor for the poet, the queen personifies the vast expertise that has traced the creator to unforeseen horizons. If the eagle represents the poet, he has an omniscient, supernatural and, undoubtedly, chosen look, about everything he will say in relation to the tyranny of Hiero. From the celestial end that this first image presents, the primary narrator takes us to the depths of the earth, the domain of the Titan Typhoon, the last and the most obstinate enemy of Zeus. We will see how Pindar manages to capture the image of Hiero from Siracusa, recognized for his despotism without betraying his own status as a great poet.